Anakinra treatment in patients with familial Mediterranean fever: a single-centre experience. (9th December 2020) - Ugurlu, Serdal; Ergezen, Bilgesu; Egeli, Bugra Han; Selvi, Oguzhan; Ozdogan, Huri
Abstract: Objectives: Anakinra is proven to be effective in controlled trials in terms of attack frequency and subclinical inflammation in colchicine-resistant patients. The objective of this study was to review the patients followed in our single centre with FMF who received anakinra because of insufficient colchicine response. Methods: The study was conducted at a tertiary rheumatology centre experienced in autoinflammatory diseases. The patients were treated for at least 1 month with anakinra. Patients with amyloidosis and pregnancy were not included. Attack frequency, patient global assessment scales of disease severity and acute phase reactants were recorded before and throughout anakinra treatment. Criteria of treatment termination were side effects, disease remission, inadequate response, pregnancy plan and non-compliance. Results: One hundred and six patients diagnosed with FMF were treated with anakinra; 45.92% of the patients had a homozygous M694V mutation; 83 of the 98 patients tested for MEFV carried at least one copy of M694V. Attack frequency decreased while on anakinra treatment; in fact, no attacks were observed in 75 patients. Visual analogue scale score decreased from 7.49 (2.03) to 3.08 (2.82) ( P  = 0.001). Currently, 71 patients are still on anakinra treatment. Treatment of 34 patients was discontinued (32%). Insufficient response and side effects were the most common reasons for treatment discontinuation. All of the side effects observed were reversible and the patients alleviated after treatment cessation. In four patients, leukopenia was observed. Conclusion: In patients who were refractory to colchicine, anti-IL-1 agent anakinra was shown to be effective and safe. The effectiveness of anakinra stems from preventing attacks and increasing the quality of life.